2022
DOI: 10.1111/een.13137
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pupal mortality in Hypena opulenta: An obstacle for establishment of a classical biological control agent against invasive swallow‐worts

Abstract: 1. Common obstacles for establishment of newly-introduced biological control agents include climate and the activity of native antagonists. In temperate climates, these obstacles can disproportionately affect overwintering life-stages because they are exposed to low winter temperatures, and may rely on passive defence from predators.2. We conducted a series of field exposure experiments with predator-exclusion treatments, in Ontario, Canada, to identify mortality factors for the pupae of Hypena opulenta, a bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(52 reference statements)
1
3
0
Order By: Relevance
“…Rearing efficiency can be maximized by storing diapausing pupae at 5 °C for 6 months, but cold storage can safely be reduced to 3 months if the rearing season needs to be extended. Our results also address key obstacles for establishment that have been identified for H. opulenta in North American release sites, such as the effects of early diapause on resource depletion, and the impacts of longer, colder winters (Jones et al, 2022). The effects of early diapause in H. opulenta on winter survival and adult fitness in regards to energy depletion may not be as detrimental as expected.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Rearing efficiency can be maximized by storing diapausing pupae at 5 °C for 6 months, but cold storage can safely be reduced to 3 months if the rearing season needs to be extended. Our results also address key obstacles for establishment that have been identified for H. opulenta in North American release sites, such as the effects of early diapause on resource depletion, and the impacts of longer, colder winters (Jones et al, 2022). The effects of early diapause in H. opulenta on winter survival and adult fitness in regards to energy depletion may not be as detrimental as expected.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, outdoor overwintering experiments using laboratory-reared H. opulenta pupae found that mortality due to cold stress was quite high (ca. 30% in the colder of two winters) (Jones et al, 2022). Finally, resource depletion in response to warm diapause conditions can take the form of accelerated consumption of carbohydrates and proteins, rather than lipids (Zhao & Wang, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the threshold photoperiod may result in only one generation per summer at more southern latitudes in North America, reducing the potential impact of H. opulenta on Vincetoxicum infestations. Other factors influencing establishment and population increase of the moth may include substantial pupal mortality, resulting from a combination of late-summer predation and overwintering mortality, and the availability of adult food sources (Jones et al 2022; Seehausen et al 2019).…”
Section: Management Optionsmentioning
confidence: 99%